TOKSOPLAZMOSIS GONDII (British Journal of Global Ecology and Sustainable Development, 2024)
Toxoplasmosis gondii causes an infectious disease called toxoplasmosis . The main hosts of this parasite are animals belonging to the feline family. The intermediate hosts are humans , mammals and birds. Toxoplasmosis is mainly spread in contries with hot and humid climates , because the oocysts live well in such an environment . Toxoplasmosis belongs to the type of simple animals , the class of spores , the family of coccidian. There are 4 ways of human transmission : oral , contact , transplacental , and airborne. The duration of the incubation period lasts from a few days to 3 weeks before the first symptoms of toxoplasma enter the body. The diseases can appear in an acute , hidden or chronic form. The disease can be acquired or congenital . Toxoplasmosis is the most dangerous during pregnancy. The reason is that it passes from the mother to the child and disrupts its development , and as a result , the child abortion also possible or it can affect the development of organs of vision , brain, and spinal cord , causing birth defects and various pathologies. Key words : Toxoplasmosis , symptoms , epidemiology , diagnosis, serological test , retinochoroiditis , antibody , IgG, IgA , IgM. Research purpose : Ways of transmission of toxoplasmosis gondii to humans , their diagnosis and the pathologies they cause in the human body. Research materials and results : In oral transmission of toxoplasmosis , fruit contaminated with its transmitted to humans mainly through undercooked meat ( such as pork , lamb , and venison) or through shellfish ( such as mussels). It can also be speared through knives , untensils , cutting boards that have come into contact with raw contaminated meat or shellfish. It is also transmitted by drinking unpasteurized goat’s milk (taxyzoites ) . Animal to human transmission ( zootnik ) . Cats play an important role in this . A cat is a parasite on itself can be infected by eating rodents , birds or other animals infected with the cat is the main host of toxoplasmosis , and it lives in the intestines of cats and produces many oocysts. It realeses the formed oocysts into the external environment through its excrement. Humans get toxoplasmosis when they change the cat’s litter box or when they eat food and water contaminated with cat faces. Oocysts can also be transmitted accidentally through soil (for example, not washing hands after gardening or eating something without washing ). Transplacental transmission , that is transmission from mother to child throughthe placenta. If a woman is infected with toxoplasmosis during pregnancy, it will be transmitted directly to the child. Abortion or stillbirth may occur later. An unborn child can also be seriously harmed. For example , early growth retardation in brain tissue , damage to or delay in the development of organs such as eyes, liver, and intestines.